Application of Central Composite Design in the Pyrolysis Process for Making Bio-Oil Based on Meranti Wood Sawdust (Shorea pinang) - Widyawati, Yeti (Agro Bali : Agricultural Journal, 2023)
Renewable energy sources are gaining importance to counteract the harmful effects of fossil fuel consumption on climate change. Among these sources, bioenergy is a viable option that can be derived from different forms of biomass and used as fuel for various purposes such as transportation, power generation, buildings, and industry. Meranti sawdust is a readily available biomass source in Indonesia that can be converted into bio-oil through pyrolytic processes. Therefore, this research aims to determine the impact of key parameters, including temperature, reaction time, and particle size, on the pyrolysis process and identify optimal yield conditions. The central composite design is the method used to determine the optimal value of the operating factors of the maximum yield of bio-oil. The results showed that the optimal conditions for the pyrolysis process are achieved at 377°C, 100 minutes of reaction time, and 0.46 mm particle size, yielding 41.48%.